DEVELOPING A ROADMAP FOR RESOLVING CONSTRUCTION WORKFORCE CHALLENGES IN NIGERIA - Oluwole ONI; Jacobus VAN WYK; Gerrit CRAFFORD (Journal of Construction Project Management and Innovation)
The inadequate supply of skilled workforce in the Nigerian house construction sector has continued to retard the productivity of the sector and exacerbated the housing challenges of the country. Nigeria has a large and fast-growing population of over 140 million with an estimated growth rate of 3.2%. This has engendered increased investment in shelter provision; especially by individuals and families due to fast rising housing rents mainly in the urban centres. Previous policies have not adequately addressed the realities of the skills inadequacies in the sector and there remains a paucity of empirical studies into the dynamics that impact construction workforce supply in Nigeria. The fallout of this is manifested in the difficulties faced by developers in sourcing suitably qualified and experienced workmen for house construction projects. In response to this challenge, an upsurge of migrant artisans and craftsmen from neighbouring West African nations like Togo, Benin Republic and Ghana - into Nigeria has occurred in the recent times. This development is totally unacceptable as it exacerbates the overarching socio-economic problems in Nigeria, especially the already high unemployment rate which is estimated to be 23.9%. This study investigates the inadequate training of house construction artisans in South Western Nigeria; and it does so by employing a quantitative research survey. It canvassed the opinions of professionals and employers. The study evolves interventions and develops a strategic blueprint for resolving the workforce crisis in the house construction sector